Flexible OLED fabrication with ITO thin film on polymer substrate - Sung Il Kim (2018)
© 2015 The Japan Society of Applied Physics. This paper reports the synthesis of flexible indium tin oxide (ITO) films in a dual pulse magnetron sputtering (DPMS) system at low temperature ( < 100 °C) deposition condition. This study also presents experimental demonstration of the ITO films for their possible use in the fabrication of organic light emitting diode (OLED) device, and the device performance on the super polycarbonate substrates. The presented data reveals the feasibility of ITO films, with a very low sheet resistance of > 30Ω/ and high transmittance of > 88% at 550 nm, simply by the magnetron pulse mode operations with increasing pulse frequency from 0 to 50 kHz.